Effect of Vitamin D and calcium supplementation on ischaemic stroke outcome: a randomised controlled open‐label trial. Issue 9 (26th August 2016) - Gupta, Anu; Prabhakar, Sudesh; Modi, Manish; Bhadada, Sanjay K; Kalaivani, Mani; Lal, Vivek; Khurana, Dheeraj
Summary: Background and aims: Vitamin D deficiency is a common problem in stroke survivors. Observational studies have reported an association of low vitamin D levels with greater stroke severity, poststroke mortality and functional disability. Randomised clinical trials are lacking. We sought to assess the effect of calcium and vitamin D supplementation in ischaemic stroke survivors with vitamin D deficiency/insufficiency on disability/mortality outcomes. Methods: In this randomised controlled open‐label trial, 73 patients of acute ischaemic stroke were screened for serum 25 hydroxy Vitamin D (25(OH)D) levels. A total of 53 patients with baseline 25(OH)D <75 nmol/L were randomised into two arms. One received vitamin D and calcium supplementation along with usual care (n=25) and the other received usual care alone (n=28). Primary outcome was the proportion of patients achieving a good outcome [modified Rankin Scale score 0–2] at 6 months and all cause mortality at 6 months. Results: The age (mean±SD) of participants was 60.4±11.3 years, 69.8% were males. The proportion of patients achieving good outcome was higher in the intervention arm (Adjusted OR 1.9, 95% CI 0.6–6.4; P =.31). The survival probability was greater in the intervention arm (83.8%, CI 62.4–93.6) as compared with the control arm (59.5%, CI 38.8–75.2; P =.049) with adjusted Hazard ratio (HR) of 0.26 (95% CI 0.08–0.9; P =.03). Conclusions: This is the first randomised controlled study assessing the effect of vitamin D and calcium supplementation on ischaemic stroke outcomes and points towards a potential benefit. Findings need to be validated by a larger trial.